IFN-γ Regulates the Expression of MICA in Human Corneal Epithelium Through miRNA4448 and NFκB - Wu, Dan; Zhang, Jing; Qian, Tingting; Dai, Yiqin; Mashaghi, Alireza; Xu, Jianjiang; Hong, Jiaxu (Frontiers in Immunology, 2018)
Purpose: Major histocompatibility complex class I-related chain A (MICA), a non-classical MHC molecule, can stimulate or co-stimulate CD8+ T cells or natural killer (NK) cells, thus affecting cornea allograft survival. This study investigated IFN-γ regulation of MICA expression levels in human corneal epithelium by miRNA4448. Methods: MICA expression levels in human corneal epithelial cells (HCECs) stimulated with IFN-γ were detected by qRT-PCR and an enzyme-linked immunosorbent assay, and differential miRNA expression levels were measured. qRT-PCR, Western blotting, and immunofluorescence staining revealed nuclear factor kappa B (NFκB)/P65 expression in IFN-γ-treated and miRNA4448-overexpressed HCECs. A luciferase reporter assay was used to predict the interaction between NFκB and MICA. Additionally, HCECs were transfected with MICA plasmid or treated with IFN-γ and NKG2D-mAb and co-cultured with NK cells and CD8+ T cells. Cell apoptosis was measured using Annexin V/PI staining. qRT-PCR detected the expression of anti-apoptosis factor Survivin and apoptosis factor Caspase 3 in MICA-transfected and IFN-γ-treated HCECs after co-culturing with NK cells and CD8+ T cells. Results: IFN-γ (500 ng/ml, 24 h) upregulated MICA expression in HCECs in vitro. Among six differentially expressed miRNAs, miRNA4448 levels decreased the most after IFN-γ treatment. The overexpression of miRNA4448 decreased MICA expression. miRNA4448 downregulated NFκB/P65 expression in IFN-γ-induced HCEC, and it was determined that NFκB/P65 directly targeted MICA by binding to the promotor region. A co-culture with NK cells and CD8+ T cells demonstrated that MICA overexpression enhanced HCEC apoptosis, which could be inhibited by NKG2D-mAb. Simultaneously, Survivin mRNA expression decreased and Caspase3 mRNA expression increased upon the interaction between MICA and NK (CD8+ T) cells in HCECs. Conclusion: IFN-γ enhances the expression of MICA in HCECs by modulating miRNA4448 and NFκB/P65 levels, thereby contributing to HCEC apoptosis induced by NK and CD8+ T cells. This discovery may lead to new insights into the pathogenesis of corneal allograft rejection.